Eliciting probabilistic expectations: Collaborations between psychologists and economists - Bruine de Bruin, Wändi (Proc Natl Acad Sci U S A, 2017)
We describe two collaborations in which psychologists and economists provided essential support on foundational projects in major research programs. One project involved eliciting adolescents’ expectations regarding significant future life events affecting their psychological and economic development. The second project involved eliciting consumers’ expectations regarding inflation, a potentially vital input to their investment, saving, and purchasing decisions. In each project, we sought questions with the precision needed for economic modeling and the simplicity needed for lay respondents. We identify four conditions that, we believe, promoted our ability to sustain these transdisciplinary collaborations and coproduce the research: (i) having a shared research goal, which neither discipline could achieve on its own; (ii) finding common ground in shared methodology, which met each discipline’s essential evidentiary conditions, but without insisting on its culturally acquired tastes; (iii) sharing the effort throughout, with common language and sense of ownership; and (iv) gaining mutual benefit from both the research process and its products.